Aktualisasi Nilai-nilai Pendidikan Islam Dalam Membentuk Pola Hidup Sederhana di Madin Al-Isnaini Montong Wasi Tahun 2020 - Azmi, Awalul; Sabeni, Ahmad (khatulistiwa, 2020)
Research conducted by the author is included in the descriptive study. In the process of data collection, the author uses the method of observation, interview, and documentation. Data analysis in this research uses qualitative descriptive analysis, namely in the form of data written and interviews from a variety of key informants or sources of information on observed behavior, so with that, the author seeks to conduct descriptive research thoroughly about the actual situation happened